The Torreya grandis genome illuminates the origin and evolution of gymnosperm-specific sciadonic acid biosynthesis - Lou, Heqiang; Song, Lili; Li, Xiaolong; Zi, Hailing; Chen, Weijie; Gao, Yadi; Zheng, Shan; Fei, Zhangjun; Sun, Xuepeng; Wu, Jiasheng (Nature communications, 2023)
Torreya plants produce dry fruits with assorted functions. Here, we report the 19-Gb chromosome-level genome assembly of T. grandis . The genome is shaped by ancient whole-genome duplications and recurrent LTR retrotransposon bursts. Comparative genomic analyses reveal key genes involved in reproductive organ development, cell wall biosynthesis and seed storage. Two genes encoding a C 18 Δ 9 -elongase and a C 20 Δ 5 -desaturase are identified to be responsible for sciadonic acid biosynthesis and both are present in diverse plant lineages except angiosperms. We demonstrate that the histidine-rich boxes of the Δ 5 -desaturase are crucial for its catalytic activity. Methylome analysis reveals that methylation valleys of the T. grandis seed genome harbor genes associated with important seed activities, including cell wall and lipid biosynthesis. Moreover, seed development is accompanied by DNA methylation changes that possibly fuel energy production. This study provides important genomic resources and elucidates the evolutionary mechanism of sciadonic acid biosynthesis in land plants. Torreya grandis is a gymnosperm species that produces edible seeds with high level of sciadonic acid (SCA). Here, the authors assemble the genome of this species, preform methylone analysis of seeds at different developmental stages, and reveal two key genes involved in SCA biosynthesis.